A Critical Consideration of the Effects of Violence in Fanon - Hofmeyr, Benda (African studies (Johannesburg), 2025)
My aim in this paper is twofold: first, I aim to establish to what extent Fanon ascribes intrinsic value to violence or whether it would be more accurate to align his position with a constructive and instrumental conceptualisation of violence. From a close reading of his 1960 address 'Why We Use Violence' (Fanon [ 1960 ] 2018 ) and the first chapter of The Wretched of the Earth ( [1961] 2004 ), a more nuanced understanding emerges that avoids the trap of the Arendtian binary scheme, which validates instrumental violence while dismissing Fanon's conceptualisation as non-instrumental. Ascribing intrinsic value to violence in Fanon decontextualises violence, which cannot be understood outside of the end it serves in the struggle for decolonisation. The intrinsic necessity of violence in colonial contexts is wrongly conflated with the intrinsic value of violence beyond instrumentality. The necessity of violence upon which Fanon insists is not an unqualified advocation of violence or a call for violence ex nihilo. Instead, he is urging the colonised to make productive use of the violence that is already given to them. Violence as Fanon conceptualises it, it will be shown, is not merely instrumental and reactive, but is also creative and constructive. In the second instance, a critical assessment of Fanon's creative and liberatory conceptualisation of violence is needed for the question remains, was Fanon right in his belief that violence in the context of the French-Algerian War would purge the African mind of the trauma colonisation inflicted, that violence is not endlessly self-perpetuating but would give rise to newly empowered subjects capable of postcolonial nation-building. To critically assess the effects of revolutionary violence, I confront Fanon's conceptualisation with the lived wartime experiences of Algerian intellectual Feraoun as documented in his Journal 1955-1962: Reflections on the French-Algerian War (2000) in the conclusive part of this paper. Feraoun concurs with Fanon that violent retaliation is a necessary condition to bring about liberation, but his testimonial reveals that revolutionary violence did not cleanse the Algerian subjects of their psychological dehumanisation, but instead spawned violent, inhumane revolutionary subjects who ended up wielding the violence they opposed against their own people.